Communication Pattern Changes Along With Declined IGF1 of Immune Cells in COVID-19 Patients During Disease Progression - Zhao, Min; Liu, Zhen; Shao, Fei; Zhou, Wenjing; Chen, Zhu; Xia, Pengyan; Wang, Shuo; Yang, Penghui (Frontiers in Immunology, 2022)
The emergence of SARS-CoV-2 which causes COVID-19 pandemic represents a global crisis. Most patients developed mild/moderate symptoms, and the status of immune system varied in acute and regulatory stages. The crosstalk between immune cells and the dynamic changes of immune cell contact is rarely described. Here we analyzed the features of immune response of paired PBMC samples from the same patients during acute and regulatory stages. Consistent with previous reports, both myeloid and T cells turned less inflammatory and less activated at recovery phase. Additionally, the communication patterns of myeloid-T cell and T-B cell are obviously changed. The crosstalk analysis reveals that typical inflammatory cytokines and several chemokines are tightly correlated with the recovery of COVID-19. Intriguingly, the signal transduction of metabolic factor IGF1 is altered at recovery phase. Furthermore, we confirmed that the serum levels of IGF1 and several inflammatory cytokines are apparently dampened after the negative conversion of SARS-CoV-2 RNA. Thus, these results reveal several potential detection and therapeutic targets that might be used for COVID-19 recovery.